The late‐Holocene decline of Tilia in relation to climate and human activities – pollen evidence from 42 sites in southern Sweden. (13th June 2017) - Hultberg, Tove; Lagerås, Per; Björkman, Leif; Sköld, Eva; Jacobson, George L; Hedwall, Per‐Ola; Lindbladh, Matts
Abstract: Aim: The dominant role of Tilia in primeval forests of Scandinavia has long been recognized, but the timing and mechanisms for its decline have not been completely unravelled. A particular uncertainty involves the balance between climate and human activities as the drivers of the change. One reason for the uncertainty is the challenge in evaluating the past cover of the genus owing to its poorly dispersed pollen; another is that a multi‐site study would be required to trace subregional differences. To overcome these obstacles, we here apply two different analytical methods to pollen data from 42 sites in two distinct vegetation zones of Sweden. Location: Temperate and hemi‐boreal vegetation zones of southern Sweden. Methods: Generalized additive mixed models (GAMM) were used to model the development of Tilia and cereal pollen percentages over time. Twelve sites were used for reconstruction of local cover of Tilia using the landscape reconstruction algorithm (LRA). Results: Before 4000 cal.bp the Tilia mean pollen percentages were similar in the two vegetation zones. Thereafter, values in the hemi‐boreal zone declined, with less Tilia since around 3000 cal.bp . In contrast, Tilia did not decrease in the temperate zone until this past millennium. The LRA application revealed that in some forests a large cover of Tilia remained considerably longer than has traditionally been estimated by pollen percentages alone. Main conclusions: By using a large coherent dataset we found significant differences in how the abundance and distribution of Tilia changed through time between two adjacent vegetation zones. We interpret the initial decline in the northern hemi‐boreal zone to be driven by cooling climate, and the later decline in the southern temperate zone to be driven more by human land‐use.